Методи оцінки рівня безпеки підприємства: підходи до управління ризиками та забезпечення стабільності - Шеренок, К. К.; Антонович, В. Д. (ХНУРЕ, 2025)
In this work, methods for assessing the security level of an enterprise are explored as essential tools for risk management and ensuring business stability. The study focuses on various aspects of security, including physical, informational, and economic protection. Key approaches such as risk analysis, scenario modeling, and the evaluation of existing security systems are discussed. The work also highlights the importance of SWOT analysis, monitoring, and auditing in identifying vulnerabilities and enhancing security strategies. Overall, these methods help minimize risks and ensure reliable protection against both external and internal threats, supporting the enterprise's continuous operation in an uncertain environment.
Keywords: безпека підприємства; управління ризиками